Pre-prison, prison, post-prison: post traumatic stress symptoms - Murphy, Daniel Shawn (2004)
Those sentenced to prison bring with them individual characteristics acquired prior to incarceration. This study assesses the effect of pre-prison experiences on adjustment to the prison environment. Regression analysis indicates that pre-prison experiences are significantly related to the likelihood of participating in, or being exposed to, elements of the incarceration experience that may cause post traumatic stress symptoms. A second component of this study assesses the relationship between elements of the incarceration experience and post traumatic stress symptoms. Regression analysis indicates that aspects of the incarceration experience constitute traumatic stressors that cause post traumatic stress symptoms in some individuals. This study also assesses the relationship between pre-prison experiences and post traumatic stress symptoms, independent of the incarceration experience, as well as assessing the relationship between a combination of the pre-prison and in-prison independent variables with development of post traumatic stress symptoms. Data for this study are drawn from surveys administered to 208 men recently released from prison in a mid-western state